Wpływ integracji na warunki życia i preferencje zakupowe Polaków - Muszyńska, Władysława (Integration's Influence on Living Conditions and Purchase Preferences of Polish Citizens, 2007)
The aim of the article is European Union integration effects' recognition concerning changes in living conditions of Polish citizens comparing to other Union's countries. Over two years of integrating process, the living condition of Polish households have been diagnosed, attitudes and purchase decision making of Polish citizens have been evaluated as well in terms of consumer's research over an international scope. As stated, the European Union integration has perspicuously influenced structural changes in living conditions in Poland and other EU countries as well.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1170, s. 53-62